2019
DOI: 10.1039/c9sm01076a
|View full text |Cite
|
Sign up to set email alerts
|

Orientational instability and spontaneous rotation of active nematic droplets

Abstract: In experiments, an individual chemically active liquid crystal (LC) droplet submerged in the bulk of a surfactant solution may self-propel along a straight, helical, or random trajectory. In this paper, we develop a minimal model capturing all three types of self-propulsion trajectories of a drop in the case of a nematic LC with homeotropic anchoring at LC-fluid interface. We emulate the director field within the drop by a single preferred polarization vector that is subject of two reorientation mechanisms, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…Besides, in the experiments of active droplets, it is also observed that the droplet can move in a helical or even chaotic trajectory at high Pe (Suga et al 2018;Maass et al 2016). Morozov & Michelin (2019b) also observed the helical and chaotic motion of the catalytic particle. Recently, the stochastic dynamics of active particles was analysed (Gaspard & Kapral 2018;Chamolly & Lauga 2019).…”
Section: A10-17mentioning
confidence: 85%
“…Besides, in the experiments of active droplets, it is also observed that the droplet can move in a helical or even chaotic trajectory at high Pe (Suga et al 2018;Maass et al 2016). Morozov & Michelin (2019b) also observed the helical and chaotic motion of the catalytic particle. Recently, the stochastic dynamics of active particles was analysed (Gaspard & Kapral 2018;Chamolly & Lauga 2019).…”
Section: A10-17mentioning
confidence: 85%
“…Also note that Eqs. (37), (41) and (39) indicate that in the lab frame the leading order flow at a distance 1/ from an active droplet is O( 4 ) (recall that at 0 the fluid is motionless), while the droplet's chemical footprint is O( ). That is, at a distance 1/ from both droplets, the advection diffusion equation, Eq.…”
Section: Asymptotic Analysis Of the Collision Dynamics For Pe ≈ Pecmentioning
confidence: 99%
“…Although velocity of the flow is small, it does not decay far away from the moving drop (recall that we use a coordinate system co-moving with the droplet). This non-vanishing flow makes it impossible to satisfy the far-field boundary conditions (15) in the framework of regular asymptotic expansion. Instead, matched asymptotic expansions are required in this case 28 .…”
Section: Asymptotic Analysismentioning
confidence: 99%
“…Robust active behavior and potential biocompatibility 7 of active droplets makes them compelling building blocks for active matter engineering. Accordingly, substantial theoretical effort is aimed at developing reliable models of active droplets 7,[10][11][12][13][14][15][16] . State-of-the-art models attribute spontaneous motion of active droplets to the Marangoni effect, that is, an interfacial flow emerging due to a chemically-induced gradient of the droplet surface tension 7,[10][11][12][13]16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation